المحكمة الجنائية الدولية بين المنطلقات الإنسانية والتحديات السياسية - أ‌. نسرين امعمر العباني (Aljameai, 2023)
المستخلص:تعتبر المحكمة الجنائية الدولية هيئة قضائية ذات أهمية بالغة، حققت نقلة نوعية في المجتمع الدولي، خاصة وأنها كانت وليدة جهود دولية مضنية من أجل منع إفلات مرتكبي الجرائم الدولية من العقاب، ومحاسبتهم على الجرائم والانتهاكات الجسيمة التي طالت العديد من البشر نتيجة الحروب والنزاعات المسلحة.عليه تحدد عنوان البحث " المحكمة الجنائية الدولية بين المنطلقات الإنسانية والتحديات السياسية "، والمقصود بتعبير " المنطلقات الإنسانية" هو ما يحمله  مضمون نظام روما الأساسي، من جملة من القيم والمبادئ الأخلاقية كالعدالة والنزاهة ونبذ العنف واستهجان العدوان ومنع الجرائم والمعاقبة عليها، وكذا الحث على التعاون المتبادل بين الدول واحترام حقوق الإنسان، وهو يعكس تطلعات كل الشعوب التي عانت ويلات الحروب وما نجم عنها من جرائم وانتهاكات جسيمة عصفت بهذه القيم الإنسانية، واستخدمت في المقابل وصف "التحديات السياسية" لتسليط الضوء على الصعوبات والعوائق ذات الطابع السياسي، التي من شأنها الحيلولة دون قيام المحكمة الجنائية الدولية الدائمة بمهامها المكلفة بها.Abstract:The International Criminal Court is a judicial body of great importance, which has achieved a quantum leap in the international community, especially it was the result of strenuous international efforts to prevent impunity for the perpetrators of international crimes, and to hold them accountable for the crimes and grave violations that affected many people as a result of wars and armed conflicts.The title of the research was determined, "The International Criminal Court between humanitarian premises and political challenges. "What is meant by the term "humanitarian premises" is what the content of the Rome Statute carries, including a set of moral values and principles such as justice, integrity, renunciation of violence, condemnation of aggression, prevention and punishment of crimes, as well as urging cooperation Mutual between states and respect for human rights, and it reflects the aspirations of all peoples who have suffered the scourge of wars and the resulting crimes and grave violations that have ravaged these human values, and used in return the description of "political challenges" to highlight the difficulties and obstacles of a political nature, which would prevent The permanent International Criminal Court performs the tasks assigned to it.